The Environment and the People in American Cities, 1600s-1900s : Disorder, Inequality, and Social Change - Taylor, Dorceta E. (Book collections on Project MUSE., 2009)
This wide-ranging study of urban environmental history draws our attention to environmental challenges faced by American cities over the past four centuries, showing how understandings of race, class, and gender shape discourse on the environment.